Measuring the health utility of chronic eustachian tube dysfunction. (22nd March 2019) - Teklu, Meron; Kulich, Marta; Micco, Alan G.; Brindisi, Kristin; Ferski, Andrew; Niekamp, Katherine; Price, Caroline P.E.; Tan, Bruce K.
Abstract : Objective: To assess the health utility of chronic Eustachian tube dysfunction (ETD). Methods: This is a prospective study of 53 patients with chronic ETD recruited from a tertiary clinic from April 2017 to July 2018. The 7‐Item Eustachian Tube Dysfunction Questionnaire (ETDQ‐7) was administered, and health utility was evaluated using the EuroQol‐5 Dimensions‐3 Level Instrument (EQ‐5D‐3L), the visual analogue scale (VAS), time tradeoff (TTO), and standard gamble (SG). Participants were grouped into medical or procedural management groups. One‐week follow‐up included repeated health utility measures and ETDQ‐7. Results: Fifty‐three patients were included in the final analysis. Of those, 34 were managed medically, and 19 received myringotomies ± PE tubes. The mean baseline ETDQ‐7 was 4.26 ± 1.31; whereas health utility measures were different depending on the method utilized: EQ‐5D‐3L 0.90 ± 0.11; VAS 0.76 ± 0.21; TTO 0.85 ± 0.23; and SG 0.94 ± 0.11 ( P < .001). There was a significant change in ETDQ‐7 ( P = .001) and TTO ( P = .011) scores posttreatment. On the ETDQ‐7, question 2 (pain in the ears) was significantly associated with VAS ( P = .032), and question 4 (ear symptoms during a cold or sinusitis) was significantly associated with TTO ( P = .006). Conclusion: Chronic ETD has a significant burden on quality of life, with a health utility similar to gastroesophageal reflux disease and moderate asthma. Although treatment‐related changes are measurable using disease‐specific quality‐of‐life measures, only TTO was significantly changed after treatment. Health utility seemed to depend on the method of measurement but provided a benchmark for evaluating cost‐effectiveness of innovations to manage ETD. Level of Evidence: 2 Laryngoscope, 130:E39–E44, 2020